Gender Budgeting: Powerful Tool for Women Empowerment: Evaluating the Impact of Gender Budgeting on Women's Empowerment (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The innovative concept of gender budgeting has received significant attention worldwide. There are about 85 countries around the world which have followed gender budgeting. Real development process can only happen when modern world considers the balance that exists between male and female. However in developing countries, they are very much deprived. The most illustrious way to bridge the gap is through Gender Budgeting Initiatives. First step towards this goal was taken by Australia, South Africa and Philippines followed by other developed and less developed countries. The issue of gender budgeting has become very much important in the present day Indian scenario for the social, economic and educational development of women as a whole. Women girls not only comprise a large part of the valuable human resources of the country, they are also individuals having their own identity their socioeconomic development sets the foundation for sustainable growth of the economy society. As a whole Gender Budgeting tends to focus on women because nearly about two third of the non-literate people in the world are women. This paper is a modest attempt to measure the effectiveness of Gender Budgeting as a tool for women empowerment.